Immediate and selective maternal brain responses to own infant faces - Valenzi, S. (2016)
Infant faces elicit caregiving in adults. In previous research on brain responses to images of infant faces, the faces were unknown to participants. This study investigated EEG in primiparous mothers of 3- to 6-month-old infants viewing their own infant's face compared to an unfamiliar but appearance-matched infant's face. Spectral power was calculated and compared, and power at three EEG bands (delta, theta, and gamma) was found to differ between faces. Brain responses among primiparous mothers distinguish images of their own versus unfamiliar infants.